Floating down the river: Vietnamese community-led social innovation. Issue 1 (19th January 2021) - Maher, Michael; Hazenberg, Richard
Abstract : Purpose: This paper aims to explore the barriers facing social enterprise-led community energy projects in Vietnam, to understand the barriers and enablers of social innovation in transitioning economies. In doing so, this paper seeks to identify whether the Vietnamese ecosystem is conducive to sustainable community energy projects and social innovation more broadly. Design/methodology/approach: This paper used a qualitative, case study-based methodology to explore institutional barriers to social innovation in the context of three community-led energy projects in Northern Vietnam. Interviews and focus groups were undertaken with 17 individual stakeholders within or engaged with the three case studies. The qualitative data used was analysed using constant comparative method, a method of analysis based in grounded theory that allows for iterative analysis of the data gathered. Findings: Social enterprises and their beneficiaries are reliant on their ability to network, but with the Vietnamese government actively involved in the markets, there are significant barriers standing in the way of these networking opportunities. Communities with little political capital are alienated from state institutions, whereas enterprises that offer alternative solutions to governmental priorities are seen as competitors by political agents. Originality/value: Applying Granovetter's theory of "embeddedness" and Herold et al. 's (2019) and Popov et al. 's (2016) theories on institutional centrality and power distribution, this paper seeks to add to our understanding on the impact large, hegemonic institutions can have on the networking ability of social enterprises and their beneficiaries.